1967
DOI: 10.1111/j.1600-0765.1967.tb01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral collagen biosynthesis in the guinea pig

Abstract: Collagen biosynthesis, as measured by conversion of 3‐4 3H‐proline to 3H‐hydroxyproline, was studied in guinea pig oral tissue and skin during normal growth, ascorbic acid depletion and following administration of ascorbic acid to scorbutic animals. Collagen breakdown in oral and skin tissue of normal animals was determined by measuring the depletion of 14C‐hydroxyproline over a seven month period of time. Oral collagen demonstrated a high level of metabolic activity, thus providing biochemical support to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Gingival connective tissue protein in man and experimental animals turns over at an inordi-nately high rate (Carneiro 1965, Claycomb et al 1967, Crumbley 1964, Page & Ammons 1975, Skougaard et al 1968). The anabolic process is accomplished by gingival fibroblasts; catabolism of collagen, the principal structural protein, results from the action of a mammalian collagenase which specifically cleaves the helical portion of native collagen moleeules but once, three-quarters of the distance from the N-terminal end (Gross & Nagai 1965, Kang et al 1966, Sakai & Gross 1967, Fullmer et al 1969.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival connective tissue protein in man and experimental animals turns over at an inordi-nately high rate (Carneiro 1965, Claycomb et al 1967, Crumbley 1964, Page & Ammons 1975, Skougaard et al 1968). The anabolic process is accomplished by gingival fibroblasts; catabolism of collagen, the principal structural protein, results from the action of a mammalian collagenase which specifically cleaves the helical portion of native collagen moleeules but once, three-quarters of the distance from the N-terminal end (Gross & Nagai 1965, Kang et al 1966, Sakai & Gross 1967, Fullmer et al 1969.…”
Section: Discussionmentioning
confidence: 99%
“…Fxperimental animal studies (Claycomb et al 1967, Page & Ammons 1974, Sodek 1976 have shown that the rate of connective tissue turnover in the gingiva is extremely high. In the marmoset only the involuting uterus and healing wounds had faster collagen turnover.…”
Section: Connective Tissue Dynamics and Repairmentioning
confidence: 99%